Metal concentration in freshwater sediments is linked to microbial biodiversity and community composition - Xin Hu; Ahmed Tlili; Kristin Schirmer; Mutai Bao; Helmut Bürgmann (Environment International)
The effect of metals on freshwater microbiomes is poorly understood compared to other factors, such as nutrients or climate. While deleterious effects of metals on plant and animal biodiversity are well documented, the role of metals in shaping the biodiversity, composition and functional potential of sediment microbial communities remains unknown. Therefore, we explored if metal concentrations can be linked to alterations in biodiversity and composition of freshwater sediment microbial communities. We collected sediments from 34 streams and lakes in Switzerland and grouped them based on their metal content. Microbial diversity and community composition were determined using 16S rRNA gene amplicon sequencing. Most of the sediments were not contaminated with metals according to Sediment Environmental Quality Criteria, although some stations exceeded the limits for Cu, Zn, and Pb. Nevertheless, correlational analysis indicated links of metal concentrations to various aspects of sediment microbial biodiversity. Al concentrations were significantly (p < 0.05) correlated with microbial richness. We further observed a predominantly negative correlation between some metals and abundances of dominant taxa. Predicted microbial functional potential analysis indicated that different types of metals have different effects on microbial functional potential. For example, Mn exhibited a significant positive correlation with nitrogen fixation potential, whereas Cu, Pb, and Zn displayed a significant negative correlation. Overall, our findings indicate that metal concentrations may alter microbial community diversity and functional potential in freshwater sediments even at ambient concentrations. Further research into the role of metals as drivers of microbial biodiversity and factors in biodiversity loss is warranted.